(untitled) (Journal of Management and Educational Sciences, 2025)
The purpose of this study is to examine the predictive role of vocational high school teachers’ levels of organizational commitment on their organizational presenteeism behaviors. The study was conducted on 295 teachers working in vocational high schools located in the Altındağ and Beypazarı districts of Ankara province. A correlational survey model was used in the study. The Organizational Commitment Scale (emotional, continuance, and normative commitment sub-dimensions) and the Organizational Presenteeism Scale (individual, organizational, and environmental presenteeism sub-dimensions) were used as data collection tools. Descriptive statistics, independent samples t-test, one-way analysis of variance (ANOVA), Pearson correlation analysis, and multiple linear regression analysis were applied to analyze the obtained data. The findings showed that organizational commitment did not predict organizational presenteeism behaviors at a significant level overall. However, it was determined that normative commitment had a positive and significant effect on individual presenteeism, while continuance commitment predicted the organizational presenteeism sub-dimension in a negative direction. No significant predictive effect was found for the other sub-dimensions. The research results show that presenteeism behaviors among teachers cannot be explained solely by organizational commitment; these behaviors emerge from the interaction of individual, organizational, and environmental factors. Accordingly, it is recommended that holistic approaches prioritizing teachers’ health and working conditions be developed.